Capital punishment - Connors, Paul; Connors, Paul G. (Farmington Hills, MI : Greenhaven Press, 2007)
Gives the pros and cons of capital punishment, the ethical question, and if it's a deterrent to crime.
Is capital punishment an effective deterrent to crime? Yes, capital punishment is an effective deterrent to crime : Capital punishment does in fact deter crime / Joanna M. Shepherd -- Homicidal violence in Great Britain has increased since the abolition of the death penalty / Theodore Dalrymple -- Hanging Saddam Hussein will deter future chaos in Iraq / Patrick Poole -- No, capital punishment is not an effective deterrent to crime : Studeis cannot "prove" capital punishment deters crime / Clive Stafford Smith -- Capital punishment is ineffective and dangerous / Michael Cohen -- Deterrence studies are inconsistent and unscientific / Jeffrey Fagan -- Should capital punishment be abolished or reformed? Executions should be televised to spur debate about capital punishment / Howard Rosenberg -- Capital punishment is a failed experiment and should be abolished / Anna Quindlen -- Feminists should advocated to abolish capital punishment / Laura Huey -- Saddam Hussein should not have been hanged / Richard Dawkins -- Public and state support for the death penalty is declining / Dahlia Lithwick.
Includes bibliographical references (p. 205-210) and index.
Keywords: Capital punishment -- United States; Capital punishment -- Moral and ethical aspects -- United States